2017
DOI: 10.1016/j.chemosphere.2017.05.083
|View full text |Cite
|
Sign up to set email alerts
|

Uptake, biotransformation and elimination of selected pharmaceuticals in a freshwater invertebrate measured using liquid chromatography tandem mass spectrometry

Abstract: Methods were developed to assess uptake and elimination kinetics in Gammarus pulex of nine pharmaceuticals (sulfamethazine, carbamazepine, diazepam, temazepam, trimethoprim, warfarin, metoprolol, nifedipine and propranolol) using targeted LC-MS/MS to determine bioconcentration factors (BCFs) using a 96 h toxicokinetic exposure and depuration period. The derived BCFs for these pharmaceuticals did not trigger any regulatory thresholds and ranged from 0 to 73 L kg−1 (sulfamethazine showed no bioconcentration). Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 64 publications
1
22
0
Order By: Relevance
“…They are, however, pseudo-persistent due to continual influx to the environment from several sources, including waste water treatment plants (WWTPs), manufacturing, agriculture and aquaculture, amongst other routes ( Boxall et al., 2012 ). Furthermore, pharmaceuticals are generally designed not to be bioaccumulative ( Lipinski et al., 1997 ), as demonstrated during in vivo laboratory exposures ( Miller et al, 2016 , 2017 ; Meredith-Williams et al., 2012 ; Nichols et al., 2015 ; Nallani et al., 2011 ). Effects are often studied and observed at non-environmentally relevant concentrations of single compounds (i.e.…”
Section: Pharmaceuticals As a Cause For Concern In The Aquatic Enviromentioning
confidence: 99%
“…They are, however, pseudo-persistent due to continual influx to the environment from several sources, including waste water treatment plants (WWTPs), manufacturing, agriculture and aquaculture, amongst other routes ( Boxall et al., 2012 ). Furthermore, pharmaceuticals are generally designed not to be bioaccumulative ( Lipinski et al., 1997 ), as demonstrated during in vivo laboratory exposures ( Miller et al, 2016 , 2017 ; Meredith-Williams et al., 2012 ; Nichols et al., 2015 ; Nallani et al., 2011 ). Effects are often studied and observed at non-environmentally relevant concentrations of single compounds (i.e.…”
Section: Pharmaceuticals As a Cause For Concern In The Aquatic Enviromentioning
confidence: 99%
“…It is suggested that the bioaccumulation of organic compounds in an aquatic environment is more related to partitioning coefficients than their absolute exposure concentrations. Furthermore, the fate of the environmental contaminants is not only affected mainly by their physio-chemical characteristics, but also biological processes including environmental parameters that play a critical role in the uptake of these chemicals [44][45][46][47]. Biological factors including individual size, life cycle, feeding type, lipid content, respiration strategy, habitat and metabolic processes may affect the uptake and sensitivity of individuals to the contaminants [48][49][50]; however, the available information is still limited [51].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it has been shown for several aquatic invertebrates, such as the insect Chironomus riparius, that exposure to sediment cannot be ignored (Leppänen and Kukkonen, 1998;Sidney, 2016). The importance of dietary uptake for aquatic invertebrates has been increasingly assessed in recent years (Ashauer 2010, Carrasco-Navarro, 2015Englert, 2017;Miller, 2017;Rösch, 2017). Chironomus sp.…”
Section: Introductionmentioning
confidence: 99%
“…The simultaneous method estimates both the uptake and elimination rates together, and is considered a potentially more reliable and more realistic model. Only recent studies (Ashauer, 2010;Miller, 2016Miller, , 2017 have applied simultaneous methods for parameter approximation. Sequential or simultaneous methods can be deployed in a frequentist or Bayesian approach.…”
Section: Introductionmentioning
confidence: 99%